2006
DOI: 10.1177/1363460706068043
|View full text |Cite
|
Sign up to set email alerts
|

Sexology, the Homo/Hetero Binary, and the Complexities of Male Sexual History

Abstract: This article re-evaluates the emphasis on the ‘homo/hetero binary’, which appears in many discussions of sexuality since the late 19th century, by exploring several key European sexological texts and their classifications of sexual desire between men. It suggests that these writers offered not so much a nascent binary between ‘homosexual’ and ‘heterosexual’ individuals, but a complex and contradictory set of sexual ontologies that encoded liminality as well as notions of innate sexual perversion. A strand of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
0
10
0
3
Order By: Relevance
“…Of the 21-works retained for analysis, five used a qualitative design (Aramburu AlegrÍa, 2013; Coleman-Fountain, 2014; L. Diamond (Blank, 2012;Brickell, 2006;Foucault, 1984), two social critiques (Fantus, 2013& Ward, 2015, one used a mixed design (Kinsey et al, 1948) and one was a presentation reporting on the emerging results of a quantitative study by Diamond (2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 21-works retained for analysis, five used a qualitative design (Aramburu AlegrÍa, 2013; Coleman-Fountain, 2014; L. Diamond (Blank, 2012;Brickell, 2006;Foucault, 1984), two social critiques (Fantus, 2013& Ward, 2015, one used a mixed design (Kinsey et al, 1948) and one was a presentation reporting on the emerging results of a quantitative study by Diamond (2013).…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion builds on the work of Kinsey et al (1948) who found that up to 37% of men had engaged in some form of homosexual encounter. Brickell (2006) proposes the existence of a hetero/homo binary and presents a detailed account of historic writing on the prevalence of homosexual behaviour among men throughout time. In fact, homosexual behaviour among men has a long history of being a culturally and socially acceptable act among affluent and powerful men.…”
Section: Hetero/homosexual Binary Of Menmentioning
confidence: 99%
“…Particularly important, perhaps, are those pioneering sexologists who named homosexuality and heterosexuality as distinctive categories of sexual belonging, with the distinguished sexologist Krafft‐Ebing, for example, arguing that men possessed both homosexual and heterosexual instinct, and that a man's final sexual preference was determined by the strongest gendered, sexual feeling. Seduction by members of the same‐sex was identified as a catalyst to ‘permanent homosexuality’ with those men ‘unable to control their passions’ being ‘sucked into an abyss of base, undifferentiated sexuality and drowned in a sea of bestial pleasures’ (Krafft‐Ebing 1892, cited in Brickell 2006, 431).…”
Section: The Heteronormal: a Brief Introductionmentioning
confidence: 99%
“…23 21 A criação do homossexual tem, como observou Jeffrey Weeks (1977:3-4), dois efeitos: "ajuda a fornecer um corte claro entre comportamento permitido e proibido e, segundo, ajuda a segregar aqueles rotulados como "desviantes" dos outros, assim contendo e limitando seu modelo de comportamento". 22 Estudos históricos recentes, como o de Chris Brickell (2006), apontam que, até fins do século XIX, ainda predominavam concepções de que a homossexualidade era algo "potencial" em todo homem, especialmente naqueles moralmente fracos, o que poderia levá-los a, nos termos da época, degenerarem. Para um estudo sobre essas ansiedades no contexto brasileiro de fins do XIX, consulte Miskolci e Balieiro, 2011.…”
unclassified